2016
DOI: 10.1103/physrevphyseducres.12.020108
|View full text |Cite
|
Sign up to set email alerts
|

Women in physics: A comparison to science, technology, engineering, and math education over four decades

Abstract: [This paper is part of the Focused Collection on Gender in Physics.] The dearth of women in science, technology, engineering, and math (STEM) fields has been lamented by scholars, administrators, policymakers, and the general public for decades, and the STEM gender gap is particularly pronounced in physics. While previous research has demonstrated that this gap is largely attributable to a lack of women pursuing physics in college, prior research reveals little in terms of the characteristics and career intere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(58 citation statements)
references
References 31 publications
2
33
0
7
Order By: Relevance
“…Women across different STEM subfields have been shown to indicate a range of career goals. Recent studies have found that most women in engineering majors do go into engineering careers, and most women in the biological sciences aspire to earn a terminal medical degree and go into health care; however, women in computing and physical sciences are more diffuse in their career interests (Kahn & Ginther, ; Lehman et al., ; Morgan, Gelbgiser, & Weeden, ; Sax et al., ). Similarly, women majoring in math are far less likely to be interested in continuing onto the graduate school in mathematics and are instead drawn to careers in business or K‐12 education (Sax et al., ; Snyder, Dillow, & Hoffman, ).…”
Section: Understanding Women Across Stem: What Do We Already Know?mentioning
confidence: 99%
“…Women across different STEM subfields have been shown to indicate a range of career goals. Recent studies have found that most women in engineering majors do go into engineering careers, and most women in the biological sciences aspire to earn a terminal medical degree and go into health care; however, women in computing and physical sciences are more diffuse in their career interests (Kahn & Ginther, ; Lehman et al., ; Morgan, Gelbgiser, & Weeden, ; Sax et al., ). Similarly, women majoring in math are far less likely to be interested in continuing onto the graduate school in mathematics and are instead drawn to careers in business or K‐12 education (Sax et al., ; Snyder, Dillow, & Hoffman, ).…”
Section: Understanding Women Across Stem: What Do We Already Know?mentioning
confidence: 99%
“…The underrepresentation of women can be seen around the world in science fields, but, in general, there are more women in the life sciences and fewer women in the physical sciences [Organisation for Economic Cooperation and Development, 2015]. A long-term survey in the US showed that the proportion of all first-year female college students who reported their intention to major in science fields (biology, computer science, engineering, math/statistics, and physics) differed depending on the field, but this figure had been consistently less than 20 percent for four decades, across all fields [Sax et al, 2016]. This study also showed that the number of female students who reported their intention to major in biology had increased from four to 16 percent from 1971 to 2011, but that the number of intended majors in physics, chemistry, and mathematics had remained at or below one percent for four decades.…”
Section: Introductionmentioning
confidence: 99%
“…There are now suggestions that the recruitment efforts should shift to certain subdisciplines of STEM (Heilbronner 2009) and focus specifically on computer science, engineering, and physics pipelines due to larger gender gaps Sax et al 2016;Su and Rounds 2015). Campbell (2011, 310) proposes a new model "Sequence of Life Events Leading to Career Choices," providing a linear progression which maps out a career path from grade school through career.…”
Section: Motivations For Career Choicementioning
confidence: 99%